La concordancia de la frase nominal por los sino hablantes aprendices de español como segunda lengua - Gutiérrez Barraza, Daniela (Colombian Applied Linguistics Journal, 2013)
In recent years the number of people who want to learn Spanish as a second / foreign language has increased. It is therefore important to study the difficulties that non-native students of Spanish have to face at the time they are involved in this process. Specifically, the native speakers students of Mandarin Chinese face particular problems because typologically it is a language different to Spanish, such as of the concordance in noun phrases. In this article I present data where there are not established relations of concordance between the elements that compose the noun phrase. Data collected from two students “but speaking” of the Spanish courses at the intermediate level in the Department of Foreign Languages at the Universidad de Sonora, consist of texts obtained from class exercises, book or prepared by the teacher responsible for the group, as well as the observation of images and videos. It was found that the structure of the nominal phrase of the “but speakers” is not different from the expected pattern in Spanish, though sometimes the relations of concordance are not set on gender and number between the nominal core and the article, or the adjective.